For the Pleasure of His Company An Affair of the Misty City, Thrice Told - Stoddard, Charles Warren 1843-1909 (Q19: The Queer American Nineteenth Century, 2023)
Charles Warren Stoddard (1843-1909) was, during his life, an acclaimed and prolific writer in multiple genres: poetry, travel sketches, personal memoir, and conversion narrative. His most popular works were dispatches primarily from the South Sea Islands but also extended into Palestine, Egypt, and what would become known as Hawai'i, most of which were published in the San Francisco Chronicle and then collected into books.For the Pleasure of His Company: An Affair of the Misty City, Thrice Told (1903) is Stoddard's only novel. This new edition, as with other works in Penn Press's series Q19: The Queer American Nineteenth Century, returns and reframes an important queer literary text to print. Set mostly in and around San Francisco in the late nineteenth century, the novel features a protagonist, Paul Clitheroe, who is an aspiring writer living among the Bohemian artistic circles of that place and time-the same circles Stoddard himself inhabited.